FAKTOR – FAKTOR ALASAN IBU GANTI CARA PIL KE IUD DI PUSKESMAS WARA UTARA KOTA PALOPO PERIODE MARET - MEI 2016 - Ny. Irmayanti; Devi Darwin; Aski Aulia Putri (Voice of Midwifery, 2017)
Today's population problem is an important issue that receives attention both around the world and Indonesia. Rapid and unbalanced population growth with increased production will lead to heavy pressures on different sectors, which in turn will make it difficult for the community to be more likely to participate. As one of the developing countries Indonesia is also not spared from the problem of population.The result of research about factors of relation of reason of mother to change way of pill to IUD In Puskesmas Wara Utara Kota Palopo Period March - May 2016, hence can be concluded, There is relation between mother knowledge with reason change contraception, contraception, There is a relationship between the role of the midwife and the reason for changing contraception. Keywords : Replacement KB, Pil, IUD